Identification of Natural Frequency and Damping Ratio using Mikrotremor on Evacuation Building Ulee Lheue and Alue Deah Teungoh - Teuku Nanta Setia; Mochammad Afifuddin; Yunita Idris (Journal of The Civil Engineering Student, 2020)
Dynamic of structure is parameter robustness building to dynamic load. That include natural frequency, and damping ratio. Dynamical structure characteristic analysis is done at escape building Ulee Lheue and escape building Alue Deah Teungoh using mikrotremor data record. The objectives are to find out the natural frequency of the building and ground beneath, and damping ratio of building. Horizontal to Vertical Spectral Ratio (HVSR) is use to process the ground data, , Floor Spectral Ratio (FSR) and Random Decrement Method (RDM) is use to process the building data. The results of ground natural frequency (f0) Alue Deah Teungoh is 4,571 Hz, and Ulee Lheue is 5,022 Hz. Natural frequency (f0) escape building Alue Deah Teungoh is 1,461 – 2,443 Hz, and escape buiding Ulee Lheue is 1,430 – 4,168 Hz. Damping ratio escape building Alue Deah Teungoh is 2,000 – 4,496 %, Damping ratio escape building Alue Deah Teungoh is 2,973 – 4,831 %.